Pleasant touch moderates the subjective but not objective aspects of body perception - Lloyd, Donna M.; Gillis, Victoria; Lewis, Elizabeth; Farrell, Martin J.; Morrison, India (Frontiers in Behavioral Neuroscience, 2013)
Un-myelinated C tactile afferents (CT afferents) are a key finding in affective touch. These fibers, which activate in response to a caress-like touch to hairy skin (CT afferents are not found in palm skin), may have more in common with interoceptive systems encoding body ownership, than afferent systems processing other tactile stimuli. We tested whether subjective embodiment of a rubber hand (measured through questionnaire items) was increased when tactile stimulation was applied to the back of the hand at a rate optimal for CT afferents (3 cm/s) vs. stimulation of glabrous skin (on the palm of the hand) or at a non-optimal rate (30 cm/s), which should not activate these fibers. We also collected ratings of tactile pleasantness and a measure of perceived limb position, proprioceptive drift, which is mediated by different mechanisms of multisensory integration than those responsible for feelings of ownership. The results of a multiple regression analysis revealed that proprioceptive drift was a significant predictor of subjective strength of the illusion when tactile stimuli were applied to the back of the hand, regardless of stroking speed. This relationship was modified by pleasantness, with higher ratings when stimulation was applied to the back of the hand at the slower vs. faster stroking speed. Pleasantness was also a unique predictor of illusion strength when fast stroking was applied to the palm of the hand. However, there were no conditions under which pleasantness was a significant predictor of drift. Since the illusion was demonstrated at a non-optimal stroking speed an integrative role for CT afferents within the illusion cannot be fully supported. Pleasant touch, however, does moderate the subjective aspects of the rubber hand illusion, which under certain tactile conditions may interact with proprioceptive information about the body or have a unique influence on subjective body perception.